1988
DOI: 10.1161/01.cir.77.2.468
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkinesis without the Frank-Starling mechanism in a nonischemic region of acutely ischemic excised canine heart.

Abstract: To determine the essential mechanism of increased systolic wall motion, i.e., hyperkinesis, in a nonischemic region (NIR) during acute ischemia, we simultaneously evaluated global and regional function ofthe excised, cross-circulated canine left ventricle connected to a volume servo pump before and after coronary occlusion. Regional areas were determined with pairs of orthogonal subendocardial sonomicrometers in the ischemic region (IR) and NIR. 468increased systolic segment shortening in a nonischemic regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…In their study, regional work for the remote area moderately decreased because LV end-systolic pressure reduced and end-systolic wall tension decreased. In the other study where LV end-diastolic volume increased to keep a stroke volume constant, they found regional work for the remote area increased (9). In our study, regional work for the remote area did not change because the change of regional endocardial surface area during a cardiac cycle for the remote area increased because of hypercontraction despite the decrease in LV pressure and wall tension at end systole.…”
Section: Regional Work Using T-a Loopsupporting
confidence: 41%
See 1 more Smart Citation
“…In their study, regional work for the remote area moderately decreased because LV end-systolic pressure reduced and end-systolic wall tension decreased. In the other study where LV end-diastolic volume increased to keep a stroke volume constant, they found regional work for the remote area increased (9). In our study, regional work for the remote area did not change because the change of regional endocardial surface area during a cardiac cycle for the remote area increased because of hypercontraction despite the decrease in LV pressure and wall tension at end systole.…”
Section: Regional Work Using T-a Loopsupporting
confidence: 41%
“…However, their method may not be appropriate as a direct measure of LV regional work, because it is only a unidirectional measurement (8). LV regional work can be reasonably assessed from the integral of wall tension with respect to the area of each region, i.e., area within a wall tension-regional area (T-A) loop (7,9,24). A previous study determined regional areas by pairs of orthogonal sonomicrometers placed on the LV endocardial surface in dogs (8).…”
mentioning
confidence: 99%
“…Tension = pressure (P) X radius (r), thus tension times area = (P X r) x r2 = PX r3 (r3 has the same units as volume) P X V, the more familiar expression of stroke work. The accuracy of RW calculated by this method was validated by Goto et al (55) in the excised cross-circulated heart using a volume servo pump system.…”
Section: Appendixmentioning
confidence: 97%
“…During ischemia, three independent factors have been identified to contribute to mechanical interaction: 1) changes in sympathetic tone, 2) the Frank-Starling mechanism, and 3) direct myocardial unloading (2,7,8,10,12,16,17,20,23,28,30). The proposed mechanism to explain mechanical interaction during ischemia is discussed for the present experimental conditions.…”
Section: Underlying Mechanismmentioning
confidence: 83%